Atoll biodiversity and environments: an AI-ready, interactive data portal for Indo-Pacific atolls - Steibl, Sebastian; Burnett, Michael W.; Holmes, Nick D.; Wegmann, Alex; Russell, James C. (Frontiers in Environmental Science, 2026)
This data article accompanies the release of an interactive, AI-ready data portal that harmonizes information on biodiversity and environments for Indo-Pacific atolls. The data portal collates species inventories using best available data for six terrestrial guilds (arthropods, birds, land crabs, native mammals, vascular plants, reptiles) alongside estimated seabird population sizes, and integrates biogeographic descriptors, land and reef habitat classifications, oceanographic variables, climate metrics, human population data, and information on historical military use. Outputs from models trained on these data are also provided, such as estimated breeding seabird population sizes for each atoll. In total, the different data layers provide information for all 310 Indo-Pacific atolls with permanent, emergent landforms, and comprise 90 standardized variables and 4,215 species records digitized from 677 literature sources, with species catalogues linked to GBIF, BOLD, and NCBI databases via unique taxon identifiers. The portal adheres to FAIR2 principles (Findable, Accessible, Interoperable, Reusable, AI-readiness, Responsible AI) to support reproducible biodiversity and environmental analyses and machine-learning workflows. While biodiversity data coverage varies geographically and both environmental and biodiversity data lack temporal replication, the dataset provides the first centralized, interoperable baseline for information on atoll biotic and physical systems, enabling a framework for additional data layers, cross-layer analyses and supporting research, conservation, climate-risk assessment, and policy.